2017
DOI: 10.1097/md.0000000000006300
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases prevalence, vaccination coverage, and diagnostic challenges in a population of internationally adopted children referred to a Tertiary Care Children's Hospital from 2009 to 2015

Abstract: Infectious diseases are common in internationally adopted children (IAC).With the objective to evaluate infectious diseases prevalence in a large cohort of IAC and to explore possible risk factors for tuberculosis (TB) and parasitic infections, clinical and laboratory data at first screening visit of all IAC (<18 years) consecutively referred to our Center in 2009 to 2015 were collected and analyzed.In total, 1612 children (median age: 5.40 years; interquartile range: 3.00–7.90) were enrolled, 123/1612 (7.60%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 52 publications
1
46
2
Order By: Relevance
“…with regard to the adoptees' countries of origin, the doses of the administered vaccines, the ages of the children and the laboratory methods used for antibody testing. The predictive value of the immunisation records of adoptees was investigated by several studies, but their findings were inconclusive, and they indicated that immunisation records may not reflect actual immunity (4,13,18,26). Many possible reasons were proposed for this, including falsifying vaccine certificates, inadequate vaccine conservation and decreased vaccine efficacy due to malnutrition (4,13,18,26).…”
Section: Adopted Children Not Included N = 38mentioning
confidence: 99%
“…with regard to the adoptees' countries of origin, the doses of the administered vaccines, the ages of the children and the laboratory methods used for antibody testing. The predictive value of the immunisation records of adoptees was investigated by several studies, but their findings were inconclusive, and they indicated that immunisation records may not reflect actual immunity (4,13,18,26). Many possible reasons were proposed for this, including falsifying vaccine certificates, inadequate vaccine conservation and decreased vaccine efficacy due to malnutrition (4,13,18,26).…”
Section: Adopted Children Not Included N = 38mentioning
confidence: 99%
“…Studies suggest that 35–42% of international adoptees have at least one infectious disease , with even an higher prevalence in those originating from Africa .…”
mentioning
confidence: 99%
“…Italy has the second highest rate of international adoption after the USA, with more than 300 adoptees every year, and has produced many publications regarding the medical care of IAC . An Italian study that assessed 1612 IAC between 2009 and 2015 found that 18% of IAC originated from Africa and half of those were from Ethiopia .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to know the vaccination status in children, so that they can be correctly immunised (9,(12)(13)(14)(15). According to our experience (9,15) This is not simple as their preadoptive immunisation records sometimes are lacking and frequently are scarcely reliable. It is helpful to keep in mind that an absent immunisation card correlates with a poor global protection.…”
mentioning
confidence: 99%